2022
DOI: 10.1039/d2cc03458a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-mild synthesis of nanometric metal chalcogenides using organyl chalcogenide precursors

Abstract: Bis(trialkylsilyl) monochalcogenides and diorganyl dichalcogenides, (R3Si)2E and R2E2 (E = S, Se or Te and R = alkyl, aryl or allyl group) have emerged in past one decade as excellent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 139 publications
0
13
0
Order By: Relevance
“…A few key synthetic approaches used for the chalcogenide nanocrystals include chemical vapor deposition, solution-based processes, hydrothermal, calcination, and hard/soft templating. 139,163,147,156,140 For example, Wang et al have reported a novel solvothermal synthesis of PIB anode materials containing octahedral CoSe 2 nanoparticles that are well-dispersed in n-doped carbon nanotubes to facilitate increased electron transport and structural stability. 140 Anodes with novel shape-controlled and hollow MoS 2 nanoparticles threaded on n-doped carbon nanotubes have also been reported.…”
Section: 2mentioning
confidence: 99%
“…A few key synthetic approaches used for the chalcogenide nanocrystals include chemical vapor deposition, solution-based processes, hydrothermal, calcination, and hard/soft templating. 139,163,147,156,140 For example, Wang et al have reported a novel solvothermal synthesis of PIB anode materials containing octahedral CoSe 2 nanoparticles that are well-dispersed in n-doped carbon nanotubes to facilitate increased electron transport and structural stability. 140 Anodes with novel shape-controlled and hollow MoS 2 nanoparticles threaded on n-doped carbon nanotubes have also been reported.…”
Section: 2mentioning
confidence: 99%
“…There is clearly on-going interest in material applications for the heavier chalcogens, e.g. as synthetic precursors for nanoparticle generation, 172 magnetic 173 and conductive materials, 174,175 in the biosynthesis of small molecules 176 and in the medicinal chemistry/biological context. 177 The aforementioned applications are complemented by the exciting recent report of the experimental imaging of the anisotropic distribution of electron density for a σ-hole for halogen atoms.…”
Section: Overviewmentioning
confidence: 99%
“…As compared to Na-based host matrices such as NaYF 4 and NaGdF 4 , there have been relatively few studies on the synthesis of lithium-based host matrices to date. ,, The precursor-directed synthesis of nanomaterials has many advantages over traditional solid-phase synthesis. It not only provides numerous opportunities for the design and improvement in the properties of these materials but also paves the way for low temperature and sustainable syntheses, thus reducing the fabrication cost and minimizing environmental pollution. While the influence of precursors on the structural and physical properties of the metal oxide and metal chalcogenide nanomaterials has been demonstrated significantly, the precursor chemistry remains scarce for the metal fluoride-based UC nanomaterials , and almost unexplored for the synthesis of LiYF 4 -based UCNPs . In this article, we describe anhydrous lithium and lanthanide trifluoroacetate complexes with a monoglyme ligand, prepared via a one-pot synthetic protocol using non-expensive commercially available reagents, as excellent precursors to bright upconverting LiYF 4 : Yb 3+ , Tm 3+ NPs by thermal decomposition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%